HARDINESS, PENYESUAIAN DIRI DAN STRES PADA SISWA TARUNA - Juniarly, Amalia; Arishanti, Novrizki (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2019)
The research objective was to determine the role of hardiness and personal adjustment towards stress. The hypothesis is there is role of hardiness and personal adjustment towards stress. The population of the study was 237 cadets of POLTEKTRANSSDP Palembang. The researcher sample was 116 students and for try out was 60 students. This study used quota sampling technique. Hardiness, personal adjustment and stress was measured by the scale wich refers to the aspects of hardiness from Kobasa, Maddi, and Khan (1982), characteristics of personal adjustment from Schneiders (1960), and symptoms of stres from Hariharan and Rath (2008). The data was analyze using multiple resgression analysis. The result of hypothesis shows that hardiness and personal adjustment have a role to the stress, with p-value=0,000 (p<0,05) R= 0,750, R square= 0,563, F=72,730. Therefore the hypothesis are accepted.